"Medication Is Just One Piece of the Whole Puzzle": How Nursing Homes Change Their Use of Antipsychotic Medications. (January 2022) - Rosenthal, Marsha; Poling, Jessica; Wec, Aleksandra; Connolly, Elizabeth; Angell, Beth; Crystal, Stephen
Antipsychotic medication use for nursing home residents with dementia poses major patient safety challenges. This article investigates health professionals' experiences with decision-making during changes under the National Partnership to Improve Dementia Care in Nursing Homes (National Partnership) and its companion state coalitions. These programs were introduced in 2012 to encourage reductions in antipsychotic use and increased use of nonpharmacological treatments for dementia. Interviews with 40 nursing home physicians and staff in seven states found that reducing antipsychotics is more time and resource-intensive than relying on medication, because it requires a person-centered approach. However, respondents supported reductions in antipsychotic use, and indicated that with sufficient staffing, effective communications, and training, they could create or implement individualized treatments. Their positive attitudes suggest that the National Partnership has been a catalyst in reducing antipsychotic medications, and their perspectives can inform further research, policy and practice in nursing homes toward achieving quality dementia care.